Physico-chemical and Biological Aspects of Monsoon Waters of AShulia for Economic and Aesthetic Applications: Preliminary Studies (Bangladesh Journal of Scientific and Industrial Research, 2008)
In the north-eastern part of Dhaka the 'Turag River' extends over Ashulia thana with a few branches. The north-eastern part of Ashulia thana mainly constitute low lands with a physiography of Madhupur Tract interlaced with Brahmaputra Floodplain. Monsoon extends over these lands from May to October and from July to October these lands remain flooded with a water depth of more than 180 cm to less than 275 cm due to surface runoff of rain water and overflow of the river canals. The area under water during this four month period can be used for economic applications such as various types of fishery as well as enhancing the present recreational applications. For these purposes the physical, chemical, and biological aspects of the water are studied to evaluate its suitability for the applications. The study was held over the period of July through December, 2006, samples being taken once every month. The physical parameters covered transparency, odor, temperature, salinity, EC, TSS, and TDS. The chemical parameters of water studied were pH, DO, BOD5, COD, hardness, NO2---N, NO3---N, PO43---P, SO42---S, Cl-, Na, K, Ca, Fe, Ni, Cu, Zn, Cd, Pb, and Hg. Among the biological parameters 'phytoplankton' and 'zooplankton' were qualitatively identified in microscopic observation up to genera. From July to October the water was transparent and of good odor, temperature ranged from 28.2°C to 24.6°C, salinity within 0.58 to 0.83 mg/L, EC within 250 to 608 ? mho/cm, TSS 0.42 to 0.82 mg/L, and TDS within 2.8 to 5.2 mg/L. Among the chemical parameters, pH ranged from 6.6 to 7.4, DO within 6.4 to 6.9 mg/L, BOD5 within 1.5 to 3.28 mg/L, COD within 3.04 to 12.89 mg/L, hardness 26.08 to 37.5 mg/L, NO2--N from undetectable to maximum 0.562 mg/L, NO3--N within 0.539 to 2.158 mg/L, PO43--P 2.35 to 2.75 mg/L, SO42--S 0.23 to 0.29 mg/L, Cl- 1.65 to 6.16 mg/L, Na 3.6 to 12.5 mg/L, K 9.7 to 11.5 mg/L, Ca 6.52 to 14.82 mg/L, Fe 0.1269 to 0.5062 mg/L, Ni 0.028 to 0.050 ?g/L, Cu 0.028 to 0.043 mg/L, Zn 0.023 to 0.048 ?g/L, Cd 0.0023 to 0.0043 ?g/L, Pb 0.043 to 0.093 ?g/L, and Hg was not detected at ppb level. Among the biological parameters a number of phytoplankton were identified covering the classes of Bacillariophyceae, Chlorophyceae, Euglenophyceae, and Cyanophyceae. The zooplanktons included the orders Cladocera and Copepoda within the class Crustacea of phylum Arthropoda. Key words: Freshwater ecology, Water resource management Bangladesh J. Sci. Ind. Res. 42(4), 377-396, 2007